Manualetto di linguistica sarda - Lupinu, Giovanni (Sardiniae memoria, 2023)
With his Manualetto, Giovanni Lupinu offers a nimble tool for students and enthusiasts who want to delve into Sardinian linguistics studies. The approach of the work is essentially historical and the organization of the subject traditional: in the first part, after providing a brief genealogical framework of Sardinian and discussing the linguistic Romanization of the island, there is a section on historical phonetics that aims to account for the elements that, from this perspective, mainly contribute to the dialectal fragmentation of the Sardinian-speaking domain; this is followed by more essential hints on morphology. The second part of the work deals with the (external) history of the language, following the model made canonical by Max Leopold Wagner: it starts from the pre-Latin substratum and goes all the way to linguistic Italianization in relatively recent times, leaving room as well for sociolinguistic considerations.